The periodic table past, present, and future - Rayner-Canham, Geoffrey (World Scientific, 2020)
"That fossilized chart on every classroom wall - isn't that The Periodic Table? Isn't that what Mendeléev devised about a century ago? No and No. There are many ways of organizing the chemical elements, some of which are thought-provoking, and which reveal philosophical challenges. Where does hydrogen 'belong'? Can an element occupy more than one location on the chart? Which are the Group 3 elements? Is aluminum in the wrong place? Why is silver(I) like thallium(I)? Why is vanadium like molybdenum? Why does gold form an auride ion like a halide ion? Does an atom 'know' if it is a non-metal or metal? Which elements are the 'metalloids'? Which are the triels? So many questions! In this stimulating and innovative book, the Reader will be taken on a voyage from the past to the present to the future of the Periodic Table. This book is unique. This book is readable. This book is thought-provoking. It is a multi-dimensional examination of patterns and trends among the chemical elements. Every reader will discover something about the chemical elements which will provoke thought and a new appreciation as to how the elements relate together"--Publisher's website